Quantitative assessment of liver function using hepatobiliary scintigraphy: the effect of microcirculatory alterations after portal vein embolization. Issue 7 (July 2019) - Rassam, Fadi; Uz, Zühre; van Lienden, Krijn P.; Ince, Can; Bennink, Roelof J.; van Gulik, Thomas M.
Abstract : Objectives: Hepatobiliary scintigraphy using technetium-99m mebrofenin has been validated as a quantitative liver function test. Preoperative portal vein embolization (PVE) is performed in patients to increase future remnant liver function and volume. Changes in hepatic microcirculation after PVE remain largely unknown and may influence the uptake of mebrofenin. The aim was to evaluate microcirculatory changes after PVE to examine differences in perfusion that might influence the uptake of mebrofenin, and consequently, assessment of function. Patients and methods: Patients undergoing liver resection with or without preoperative PVE were included. Future remnant liver volume and function were measured before and after PVE. Hepatic microcirculation was measured in the embolized and the nonembolized lobes during resection. Microcirculatory flow index, perfused vessel density, sinusoidal diameter and red blood cell velocity were assessed. Results: A total of 16 patients, eight with preoperative PVE and eight control patients without PVE, were included. After PVE, both function and volume of the nonembolized lobe were significantly increased, and the functional increase exceeded the increase in volume. Perfused vessel density and sinusoidal diameter were significantly higher in the nonembolized liver lobe ( P <0.002 and <0.04). No significant differences between both lobes were found concerning microcirculatory flow index or red blood cell velocity. Conclusion: After PVE, the nonembolized lobe had a significantly higher (functional) microvascular density compared with the embolized lobe, without differences in microvascular flow. These findings indicate that the measured functional increase using hepatobiliary scintigraphy, which exceeded the volumetric increase, was not the consequence of an increase in hepatic perfusion, therefore, providing adequate representation of the liver function.